Severe Childhood Asthma in Low and Middle-Income Countries - Mallol-Villablanca, E (W.B. Saunders Ltd, 2025)
Although severe asthma in low- and middle-income countries (LMICs) is relatively uncommon in children and adolescents (2.1 % and 4.3 %, respectively), it results in significant morbidity, occasional fatality, and great challenges of management, compared to high-income countries. Additionally, nearly 6 % of infants in LMICs experience nighttime symptoms on a weekly basis. Socioeconomic inequities and exposure to environmental risk factors contributed to variability in prevalence, with children from disadvantaged backgrounds being at a higher risk of developing the condition. Numerous preventable risk factors have been identified in these regions, including tobacco smoke, indoor and outdoor pollution (e.g., the use of biomass fuels), allergens, diet, and urbanization, among other lifestyle factors. Almost half of the patients with severe asthma received inadequate treatment. For example, only 55 % use inhaled corticosteroids (ICS), and while most physicians prefer pressurized metered-dose inhalers, only a third recommend using spacers. In some countries, oral short-acting beta agonists and theophylline are still used as treatment options. Compared to fixed-dose ICS/long-acting beta-agonists (LABA), maintenance and reliever therapy (MART), adding tiotropium, and triple therapy (ICS + LABA + LAMA) are cost-effective options in LMICs. Biologic drugs are expensive and have limited access, and studies have shown that omalizumab and dupilumab are not cost-effective treatments in LMICs. Barriers to adequate follow-up include poorly organized health services, limited spirometry, and patients’ non-compliance. Public health efforts should prioritize improving access to affordable asthma medications, enhancing diagnostic capacity in underserved areas, and addressing environmental risk factors that contribute to asthma. © 2025 Elsevier Ltd